Foodborne zoonoses control in low- and middle-income countries: Identifying aspects of interventions relevant to traditional markets which act as hurdles when mitigating disease transmission - Leahy, Eithne; Mutua, Florence K.; Grace, Delia; Lambertini, E.; Thomas, Lian F. (Frontiers Media, 2022)
Globally, foodborne zoonoses are responsible for approximately one third of all foodborne disease burden and this picture is likely to worsen if consumption of animal source foods continues to rise with insufficient attention to risk mitigation. Traditional markets represent highly important nodes that can be targeted for risk mitigation; in this series of case studies, we discuss food safety interventions relevant to this nexus. We illustrate that to improve food safety within traditional markets it is essential to consider some of the motivations and incentives of the stakeholders involved and the cultural, social, and economic context in which interventions are undertaken, highlighting barriers, enablers future interventions should aim to avoid, embrace. We also conclude that a holistic approach to foodborne zoonoses control will require the institutionalization of One Health across food systems of which traditional markets are part.